Verbal and Figural Creativity in Children With Autism Spectrum Disorder and Typical Development - Kasirer, Anat; Adi-Japha, Esther; Mashal, Nira (Frontiers in Psychology, 2020)
Previous studies have shown that individuals with autism spectrum disorder (ASD) demonstrate lower performance on creativity tasks. However, recent findings suggest that individuals with ASD are not necessarily impaired in verbal creativity, as measured by the novel metaphor generation task. The current study investigates verbal and figural creativity in 40 children with ASD (aged 11-14 years) and 39 peers with typical development (TD) (aged 11-15 years). We also tested the contribution of executive functions to the creative performance. A sentence completion questionnaire was used to test creative verbal generation, while a task of drawing nonexistent objects was used to assess figural abilities. The results indicate that children with ASD generated a greater quantity of creative metaphors and showed greater use of a specific kind of representational change on the figural creativity task: cross-category insertions (e.g., a house with a tail). However, no correlation was found between the metaphor generation task and the use of cross-category insertions for either group. Results also showed that, whereas phonemic fluency contributed to the explained variance in novel metaphor generation in the ASD group, ﬂuid intelligence, although only marginally, contributed to variance in novel metaphor generation in the TD group. These findings suggest that verbal creativity and figural creativity are two separate abilities relying on different cognitive resources. Our results show that those with ASD and TD differ in the cognitive abilities they use to perform the metaphor generation task. The research points to a unique creative cognition profile among children with ASD.